Discrepancies in glycemic metrics derived from different continuous glucose monitoring systems in adult patients with type 1 diabetes mellitus. Issue 7 (21st July 2022) - Zhou, Yongwen; Mai, Xiaodong; Deng, Hongrong; Yang, Daizhi; Zheng, Mao; Huang, Bin; Xu, Linlin; Weng, Jianping; Xu, Wen; Yan, Jinhua
Abstract: Background: Continuous glucose monitoring systems have been widely used but discrepancies among various brands of devices are rarely discussed. This study aimed to explore differences in glycemic metrics between FreeStyle Libre (FSL) and iPro2 among adults with type 1 diabetes mellitus (T1DM). Methods: Participants with T1DM and glycosylated hemoglobin of 7%–10% were included and wore FSL and iPro2 for 2 weeks simultaneously. Datasets collected on the insertion and detachment day, and those with insufficient quantity (<90%) were excluded. Agreements of measurement accuracy and glycemic metrics were evaluated. Results: A total of 40 498 paired data were included. Compared with the values from FSL, significantly higher median value was observed in iPro2 (147.6 [106.2, 192.6] vs. 144.0 [100.8, 192.6] mg/dl, p < 0.001) and the largest discordance was observed in hypoglycemic range (median absolute relative difference with iPro2 as reference value: 25.8% [10.8%, 42.1%]). Furthermore, significant differences in glycemic metrics between iPro2 and FSL were also observed in time in range (TIR) 70–180 mg/dl (TIR, 62.8 ± 12.4% vs. 58.8 ± 12.3%, p = 0.004), time spent below 70 mg/dl (4.4 [1.8, 10.9]% vs. 7.2 [5.4, 13.3]%, p < 0.001), time spent below 54 mg/dl (0.9 [0.3, 4.0]% vs. 2.6 [1.3, 5.6]%, p = 0.011), and coefficient of variation (CV, 38.7 ± 8.5% vs. 40.9 ± 9.3%, p = 0.017). Conclusions: During 14 days of use, FSL and iPro2 provided different estimations on TIR, CV, and hypoglycemia‐related parameters, which needs to be considered when making clinical decisions and clinical trial designs. Abstract : Highlights The accordance between the paired dataset between FSL and iPro2 was acceptable but poorer in hypoglycemic range. Significant differences for glycemic metrics between iPro2 and FSL were observed in time in range 70–180 mg/dL, coefficient of variation, and hypoglycemia‐related parameters (including time below range 54 mg/dL and 70mg/dL). The study reminded us when using the CGM for clinical decisions and clinical trials, it is necessary to consider the model heterogeneity. 摘要: 背景: 连续血糖监测系统已被广泛使用，但不同品牌的设备之间的差异很少被讨论。本研究旨在探讨成人1型糖尿病(T1DM)患者中Freestyle Libre(FSL)和iPro2在血糖指标上的差异。 方法: 选择T1DM和糖化血红蛋白(HbA1c)为7% 10%的受试者，同时使用FSL和iPRO 2两周。排除了在植入和取出当天收集的数据集，以及质量不够高(<90%)的数据集。对测量准确度和血糖指标的一致性进行评估。 结果: 共纳入40498对数据。与FSL相比，iPro2的中位数显著升高(147.6[106.2, 192.6]vs 144.0[100.8, 192.6]mg/dL，P<0.001)，其中不一致性最高的是低血糖范围(以iPro2为参考值的绝对差值中位数:25.8% [10.8%, 42.1%])。此外，iPro2和FSL在70‐180 mg/dL达标时间(TIR)内的血糖指标也有显著差异(TIR，62.8±12.4vs.58.8±12.3%，P=0.004)，在70 mg/dL以下的时间(4.4 [1.8, 10.9]% vs.7.2[5.4，13.3]%，P<0.001])，在54 mg/dL以下的时间(0.9[0.3，4.0]% vs.2.6[1.3，5.6]%, p=0.011)，变异系数(CV, 38.7±8.5% vs.40.9±9.3%，P=0.017)。 结论: 在使用的14天中，FSL和iPro2对TIR、CV和低血糖相关参数提供了不同的估计，在临床决策和临床试验设计时需要考虑这些因素。